Relevance and Adaptation of Sorogan Method in Modern Islamic Boarding Schools: Opportunities and Challenges - Ulhaq, Muhammad Miftah; Rizal Nurzain; Melinda Koestanti; Taufiqurrahman; Tarsono (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to identify Santri's perceptions of the challenges and opportunities in learning the sorogan method in Modern Islamic Boarding Schools. The research method is a descriptive qualitative approach with data collection through in-depth interviews, observation, and documentation studies. Data analysis was conducted through thematic coding to find the main patterns of santri perceptions related to the implementation of the sorogan method. The results showed that sorogan has significant advantages as an individualised learning method, especially in improving in-depth understanding of the yellow classical books and shaping santri characters, such as patience, discipline, and responsibility. However, the challenges faced include time constraints due to the tight schedule combining formal and diniyah curricula and the need to adapt to technology. On the other hand, great opportunities are seen in integrating technological elements, such as audio or video recordings and learning applications, which can complement the effectiveness of this method. This research also proposes the Hybrid Sorogan model, which combines the traditional sorogan approach with modern technological innovations, to answer the needs of Modern Islamic Boarding Schools without losing the core values of this method. The research conclusion confirms that the sorogan method remains relevant and adaptive to the needs of the times, provided that strategic and innovative management is carried out. The findings contribute to the pesantren education literature and offer practical guidance for developing tradition-based learning methods in a modern context.